The Effect of Employee Competence and Motivation, as well as Leadership, on Employee Performance in the Simalungun Regency Government - Hengky Kurniawan Sitanggang (Green Publisher Indonesia, 2026)
Employee performance in government institutions plays a critical role in achieving organizational goals and delivering public services effectively. In the context of the Simalungun Regency Government, the performance of employees is influenced by various factors such as competence, motivation, and leadership. This Journal aims to analyze the influence of employee competence and motivation, as well as leadership on employee performance in the Simalungun Regency Government. The method used in this study is quantitative. The sample of this study amounted to 202 people. Data were analyzed using descriptive analysis and statistical analysis of SPSS version 25. The results of the study concluded that the competency variable (X1) had a significant effect on the performance of Simalungun Regency employees. Based on the results of the analysis, the calculation was obtained 2,200 with a value of sig. by 0.029. The motivation variable (X2) has a significant effect on the performance of Simalungun Regency employees. Based on the results of the calculation analysis, a t-value of 2.933 was obtained with a value of sig. by 0.004. The leadership variable (X3) has a significant effect on the performance of Simalungun Regency employees. Based on the results of the analysis, the calculation was obtained 2,200 with a value of sig. by 0.029. Based on the table above, a calculated t value of 3.950 with a sig value was obtained. by 0.000. Simultaneously, competence (X1) and motivation (X2) and leadership (X3) have a significant effect on the performance of Simalungun Regency employees.